PERKEMBANGAN KEJAHATAN TEKNOLOGI INFORMASI (CYBER CRIME) DAN ANTISIPASINYA DENGAN PENAL POLICY - Supanto, Supanto (Faculty of Law, Universitas Sebelas Maret, 2016)
AbstractThe research conducted to inventory of the various laws (the legislative products) relating to the regulating in the field of information technology crime, to identify its adjustment in globalization, to describe the conduct proscribed as a crime of the Information and Electronic Transaction, as well as reviewing the formulation of criminal sanctions. Studies based on the idea that regulation Law Number 11 of 2008 is aimed at setting the utilization of information technology, particularly the information and electronic transactions, in order to be implemented properly and maintain the safety and benefit of humanity. However, their use potentially criminal, which must be addressed, including the use of criminal law, therefore there is a provision in the law of criminal sanctions, in this case defined the prohibited acts and penalties specified criminal, offense. Conclusions obtained, In line with an information technology and The Law of Infromation and Transaction of electronic (The Law No. 11 of 2008/UU ITE), inventoried some legislation which can be understood as an attempt arrangement of information technology, especially as a crime, as in the Criminal Code (KUHP), the Law on Telecommunications, the Law on Copyright / patent, the law of terrorism . The adjustment of The Law Number 11 of 2008 on the Information and Electronic Transactions with global regulation and a comparative assessment of the demands that must be met in order to harmony especially on the cyber crime law. In addition, the formulation of a threatened criminal sanctions in offenses under the Act remain as types of criminal sanctions prescribed in the Penal Code, which is a kind of imprisonment sanction fines and criminal sanctions, but not formulated an additional criminal sanction. Therefore, its system is no innovation typical types of criminal sanctions for offenses in the field of information and electronic transactions. AbstrakPenelitian yang dilakukan bertujuan untuk menginventarisasi berbagai undang-undang (produk legislatif) yang berkaitan dengan bidang kejahatan teknologi informasi, untuk mengidentifikasi penyesuaian dalam era globalisasi, untuk menggambarkan perilaku terlarang sebagai kejahatan Informasi dan Transaksi Elektronik , serta meninjau perumusan sanksi pidana. Studi didasarkan pada gagasan bahwa UU Nomor 11 Tahun 2008 bertujuan untuk pengaturan pemanfaatan teknologi informasi, khususnya informasi dan transaksi elektronik, agar dapat dilaksanakan dengan baik dan menjaga keamanan dan kepentingan kemanusiaan, namun penggunaannya berpotensi pidana, termasuk penggunaan hukum pidana, karena ada ketentuan dalam hukum sanksi pidana, dalam hal ini didefinisikan tindakan yang dilarang dan hukuman yang ditentukan pidana. Kesimpulan yang diperoleh, Perlu penyesuaian UU Nomor 11 Tahun 2008 tentang Informasi dan Transaksi Elektronik dengan regulasi bersifat global dan penilaian komparatif dari tuntutan yang harus dipenuhi untuk keharmonisan terutama pada hukum kejahatan cyber. Dalam UU ITE, terhadap perbuatan yang dilarang diancam sanksi pidana. Adapun jenis sanksi pidananya adalah sanksi pidana penjara dan sanksi pidana denda. Jenis sanksi ini sudah dikenal dalam Pasal 10 KUHP, dan tidak ditentukan jenis pidana tambahan. Dengan demikian tidak ada pengembangan mengenai jenis pidana khusus yang ditujukan bagi pelaku tindak pidana di bidang informasi dan transaksi elektronik.